A teologia do encontro na pessoa de Jesus Cristo a partir do pensamento de Paul Ricoeur - Lemos, André Luiz (2024)
This dissertation aims to present the theology of encounter in the person of Jesus, uniting the biblical accounts and the thoughts of Paul Ricoeur. We will address recognition and otherness as instruments for the becoming of a new human being. The research problem was formulated as follows: does the existence of the other compel us to encounter and enable us to recognize this other as the basis of the pastoral work of Jesus Christ and the Church in its evangelizing dimension? The methodology is limited to bibliographical research in four interlocutor dimensions, namely: Biblical, Philosophical, Theological and Pastoral. We will use Sacred Scripture and the works of Paul Ricoeur, specifically: Percurso do Reconhecimento (2006); Biblical hermeneutics (2006) and The self as another (1991). The expected results consist of understanding that whoever is found has the experience of rethinking their history and, thus, opens up to others and to the world. Faced with such a selfish humanity, the theology of encounter presents itself as a tool for the missionary dimension of the Church to create, in human beings, the capacity for fraternity and liberation, leading them to their self-realization before God